Integrating explicit contextual priors and kinematic information during anticipation - Gredin, N. V.; Bishop, D. T.; Williams, A. M.; Broadbent, D. P. (Journal of Sports Sciences, 2021)
We examined the interaction between explicit contextual priors and kinematic information during anticipation in soccer. We employed a video-based anticipation task where skilled soccer players had to predict the direction of the imminent actions of an attacking opponent in possession of the ball. The players performed the task both with and without explicit contextual priors pertaining to the opponent`s action tendencies. The strength of the opponent`s action tendencies was altered in order to manipulate the reliability of contextual priors (low vs. high). Moreover, the reliability of kinematic information (low vs. high) was manipulated using the temporal occlusion paradigm. The explicit provision of contextual priors biased anticipation towards the most likely direction, given the opponent`s action tendencies, and resulted in enhanced performance. This effect was greater under conditions where the reliability of kinematic information was low rather than high. When the reliability of kinematic information was high, the players used explicit contextual priors of high, but not low, reliability to inform their judgements. Findings suggest that athletes employ reliability-based strategies when integrating contextual priors with kinematic information during anticipation. The impact of explicit contextual priors is dependent on the reliability both of the priors and the evolving kinematic information.